Outcome and Management of Babies with Prenatal Ultrasonographic Renal Abnormalities - Lam, Barbara C.C.; Wong, Sik-Nin; Yeung, Chap-Yung; Tang, Mary H.Y.; Ghosh, A. (American Journal of Perinatology, 1993)
Between January 1987 and December 1990, 60 fetuses were found to have renal abnormalities on antenatal ultrasonography. Six fetuses were aborted because of major renal abnormalities with or without associated chromosomal aberrations. Twelve babies with major renal abnormalities died in the immediate neonatal period. Forty-two babies were studied after birth and followed up. Babies who were found to have mild dilation of the renal pelvis of 6 to 10 mm during fetal life revealed either normal renal findings in the postnatal period or complete resolution of the abnormalities within the first year. Significant pelvic dilation of more than 10 mm occurred in 32 babies. A significant proportion (34%) had transitional hydronephrosis that resolved spontaneously during the follow-up period (mean, 2œ years; range, Iœ to 4œ years). Extrarenal pelvis, another benign condition, accounted for 15.6%. Most babies with pelviureteral junction obstruction (15%) and vesicoureteral junction obstruction (6.2%) required early neonatal surgery. The technetium-99m diethylenetriamine renal scan with the diuretic renogram half-time was found to be a very useful tool to distinguish between obstructive and nonobstructive hydronephrosis. With early diagnosis and intervention, the prognosis for many of these renal abnormalities is much more favorable and such information is invaluable for antenatal counseling.